In-Situ Observation of New Extra-Vascular Threadlike Structure of Mouse Using a Fluorescence Stereoscopic Microscope - Baeckkyoung Sung; Jawoong Lee; Byung-Cheon Lee; Hyun-Min Johng; Ku-Youn Baik; Tae Jeong Nam; Dae-Hun Park; Kyeong-Sun Soh; Kwang-Sup Soh (Korean Pharmacopuncture Institute, 2004)
We report the new threadlike structures outside the blood vessels of mice. For this, we developed an in-situ searching method of the structure by vital staining with the dye of acridine orange and using a fluorescent stereomicroscope designed specifically for this purpose. We consider that the newly found threadlike structure might be rediscovery of the extra-vascular Bonghan duct which was reported in 1963 by Bonghan Kim.